The Moral Economy of Everyday Crime : Markets, Consumers and Citizens - Karstedt, Susanne (The British journal of criminology, 2006)
Between the crimes in the suites and the crimes in the streets lies the mostly unexplored terrain within which we find crimes of everyday life'. Not all of these are formally illegal, but all are generally seen as morally dubious. Most of the crimes of everyday life are committed in the contemporary marketplace, and by those who think of themselves and are mostly considered by others as respectable citizens. We contextualize normative orientations that are conducive to such types of behaviour using a framework that links E. P. Thompson's 1963 concept of the moral economy' with Institutional Anomie Theory Messner and Rosenfeld 1994, 2007. Findings from a comparative survey study in three economic change regions England and Wales, Western and Eastern Germany show that a syndrome of market anomie comprising distrust, fear and cynical attitudes toward law increases the willingness of respectable citizens to engage in illegal and unfair practices in the marketplace